Steinbeck at the Nobel Prize Ceremony - unknown:::Creator::::::::::::
John Steinbeck walking up steps and holding the Nobel award in his right hand. Behind him men are clapping. The caption on the back reads: "Nobel Prize Ceremony, 1962. Stanford University Libraries."